Analisis Hots Pada Pre-Activity Dalam Buku Siswa “English Skills For The Future” Kelas XII - Siti Aisyah Nur Aini; Sri Handayani (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
This study aims to analyze the distribution of Higher Order Thinking Skills (HOTS) in each question on pre-activity in the student book entitled "English Skills For the Future" edition for class XII Senior High School. Qualitative descriptive methods were used in this study with documentation technique in a document in the form of student book entitled "English Skills For the Future" for class XII. The HOTS theory (C4 = analyze, C5 = evaluate, and C6 = create) in Anderson & Krathwohl's revised Bloom's taxonomy was used as a reference for analyzing the data. This study focused on data sourced from the Swing Into Action section contained in all chapters in the student book with a total of 37 data questions. The results of this study showed that 30% of the questions were C4, 32% of the questions were C5, and 38% of the questions were C6. Based on the results of the analysis, it could be concluded that the questions distributed on pre-activity in the student book "English Skills For the Future" edition for class XII SMA all contain HOTS based on Anderson & Krathwohl's revised Bloom's taxonomy, with the dominance of category C6 (create) questions in HOTS.